Problems of Online Learning in The Perspective of English Education Students IKIP Budi Utomo Malang - Firdaus, Ghea Suramita; Zhahira, Dea Athaya; Anggraini, Anita Larasati Dwi; Hadiwijaya, Munawwir (IJET (Indonesian Journal of English Teaching), 2022)
The Covid-19 pandemic has prompted the government to make regulatory changes in several aspects, including education aspect in Indonesia. The government implements a new policy, namely online learning, including at the university level. Although it is effective in stopping the spread of Covid-19, it turns out that there are still many problems that students must face in its implementation. This study used descriptive qualitative method. Collecting data using questionnaires and interviews. The data collected will be analyzed using descriptive statistics. The subjects in this study were students of English Education IKIP Budi Utomo. Through this research, the problems faced by students can be recorded. The results showed that the problem faced by students was the decreased in academic motivation caused by the inability of students to participate in online learning. Many students admit that they are less focused, constrained by the internet connection and quota, and inadequate learning media.